Analysis of purse seine fisheries business feasibility in coastal fishing port Pondok Dadap, Sendang Biru, East Java, Indonesia - Imam Nurul Firdaus; Dony Prasetyo; Ganjar Adhywirawan Sutarjo; David Hermawan (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
A purse seine is a fishing tool made of nets which are operated by circling the hordes of fish to a bowl-shaped tool at the end of the fishing process and is commonly used to catch pelagic fish by fishermen at UPT PPP Pondokdadap. The purpose of this study was to determine the technical aspects and income of the purse seine vessels in Sendang Biru village and to analyze the feasibility of the purse seine fishery business in the Sendang Biru village. This research was conducted from May to June 2019 at UPT PPP Pondokdadap, Sendang Biru, Malang Regency. The research sample was taken by purposive sampling. Data analysis using descriptive analysis and business financial analysis. The results of the calculation of the business analysis and investment on the purse seine ship found a profit of IDR 1,394,798,872, R/C of 43, PP of 13 months, ROI of 92, NPV of IDR 90,337,780,072, IRR of 633.8 %, and Net B/C is 61. The results show that the purse seine fishery business meets the requirements and is still feasible to be implemented.